A case of acquired phonological dyslexia with selective impairment of Kanji: analysis of reading impairment mechanism using cognitive neuropsychological models for reading. Issue 2 (4th March 2022) - Uema, Shinji; Uno, Akira; Hashimoto, Kosei; Sambai, Ami
ABSTRACT: We report a Japanese-speaking patient who showed acquired phonological dyslexia only in Kanji; difficulty in reading two-character Kanji nonwords despite her ability to read Kana nonwords, Kana words, and two-character Kanji inconsistent-atypical words; and inability to repeat reversal nonwords. We investigated the mechanism of nonword reading impairment using the dual-route cascaded model, it was likely that the reading deficit of Kanji nonwords with multiple pronunciations resulted from the dysfunction of the character-to-sound conversion rule system. The patient's reading performance on the dissociation of Kana and Kanji was considered to reflect the difference in the consistency of orthography-to-phonology mapping.